2003
DOI: 10.1016/s0925-5273(03)00110-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vendor managed inventory (VMI) dynamics on the Bullwhip Effect in supply chains

Abstract: The paper compares the expected performance of a Vendor Managed Inventory (VMI) supply chain with a traditional "serially-linked" supply chain. The emphasis of this investigation is the impact these two alternative structures have on the "Bullwhip Effect" generated in the supply chain. We pay particular attention to the manufacturer's production ordering activities via a simulation model based on difference equations. VMI is thereby shown to be significantly better at responding to volatile changes in demand s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
180
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(190 citation statements)
references
References 31 publications
3
180
0
7
Order By: Relevance
“…They concluded that the appropriative delay depends on the level of aggregation and order scheduling. (Disney and Towill, 2003a) and (Disney and Towill, 2003b) produced two articles regarding VMI and the bullwhip effect. The first article demonstrates, through mathematical modeling and simulation that VMI helps to dampen the bullwhip effect focusing on that portion of the bullwhip effect created by what the authors term the "Forrester effect" (consisting of non-zero lead times and demand signaling processing).…”
Section: Discrete Event Simulationmentioning
confidence: 99%
“…They concluded that the appropriative delay depends on the level of aggregation and order scheduling. (Disney and Towill, 2003a) and (Disney and Towill, 2003b) produced two articles regarding VMI and the bullwhip effect. The first article demonstrates, through mathematical modeling and simulation that VMI helps to dampen the bullwhip effect focusing on that portion of the bullwhip effect created by what the authors term the "Forrester effect" (consisting of non-zero lead times and demand signaling processing).…”
Section: Discrete Event Simulationmentioning
confidence: 99%
“…We take the Order Variance Ratio (OVR) applied by Chen et al [4,5] to measure the bullwhip effect of the supply chain, and the Inventory Variance Ratio (IVR) proposed by Disney and Towill [32] to measure the amplification of demands on the inventory. In this section, the OVR and IVR of the whole supply chain will be investigated under different states:…”
Section: Experimental Design Numerical Results and Discussionmentioning
confidence: 99%
“…ERP software usage with techniques such as vendor managed inventory, just-in-time purchase, SCM software can considerably influence reducing the time and information delays which as a result mitigate the bullwhip effect (McCullen & Towill, 2002;Disney & Towill, 2003a;Disney & Towill, 2003b;Ravichandran, 2008). Furthermore, ERP helps in improving order management and cycle times (Kelle & Akbulut, 2005;Ravichandran 2008;Tarantilis, Kiranoudis, & Theodorakopoulos, 2008) and it can reduce procurement costs (Baudmann, Ahsen, & Diaz, 2004 Though digital actions can positively influence e-business value creation in terms of increasing sales, consumers will migrate to being more active participants and creators of content as social media increasingly becomes the backbone of digital experience.…”
Section: Influence Of Erp On Mitigating Bullwhip Effectmentioning
confidence: 99%